Individual Foreign Policy Analysis of Donald Trump: A Case Study of the US Embassy relocation to Jerusalem - Abdiel, Kenny Setya (Jurnal Hubungan Internasional, 2020)
In the context of foreign policy, the Trump administration has made various pro-Israel moves starting with the relocation of the US embassy for Israel to Jerusalem in late 2017. These high-risk policies frequently denounced by the international community. Despite that, Trump persisted in generating such policy, which was influenced by his personal dimension. This study aims to examine how Trump’s personality, precisely his leadership style, affects the decision to relocate the US Embassy to Jerusalem and other pro-Israel policies. In answering the question, this study adopted a political psychology approach by using psychobiography and content analysis as complementary methodologies. The approach was meant to build a complete picture of a leader’s political behavior. It was found that Trump often neglected facts and information on the ground. Therefore, he could be categorized as an aggressive leader who is willing to take risky decisions, although he is aware of the consequences. His inadequacy in organization management also increases the intensity of high-risk policies. In addition to that, Trump’s policies are motivated by his desire to secure political support amongst Judeo-Christian interest groups.